Relevansi Nilai Religius pada Novel “Cinta Suci Zahrana” Karya Habiburrahman El Shirazy sebagai Bahan Ajar Bahasa Indonesia di SMA - Al Gadri, Henri Henriyan; Wiharja , Irpa Anggriani; Saraswati (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
This study examines the relevance of religious values ​​in the novel Cinta Suci Zahrana by Habiburrahman El Shirazy as Teaching Materials in Senior High School. The method used in this study is descriptive qualitative analysis. Qualitative descriptive analysis techniques are used to describe the data that has been found. This study shows the religious values ​​in the novel Cinta Suci Zahrana and its relevance as open Indonesian language materials in Senior High School. The religious values ​​found are religious values ​​related to God, religious values ​​related to oneself, and religious values ​​related to humans and the environment. These religious values ​​are relevant to learning Indonesian literature in senior high school class XI, namely Basic Competence 3.7 Analyzing the values ​​(cultural, social, moral, religious, and educational) of the novel.